Digital Mental Health Interventions: Bridging the Gap in Adolescent Mental Health Services in Nigeria - Ojo-Rowland, O. T.; Sawyerr, D. O.; Kazeem, S. A.; Akinleye, E. D.; Akporugo, P. O.; Morenikeji, D. O.; Akinbohun, O; Adeyemi, E. O. (British Journal of Healthcare and Medical Research, 2026)
Adolescence (10–19 years) represents a critical developmental period marked by significant physical, emotional, and social transitions, during which mental health challenges such as anxiety, depression, and behavioural disorders frequently emerge. In Nigeria, these challenges are compounded by socioeconomic stressors, limited mental health infrastructure, and pervasive stigma, resulting in a substantial treatment gap. Despite the growing burden, access to adolescent mental health services remains critically inadequate due to shortages of trained professionals, poor service integration, and weak policy implementation. This study explores the potential of digital mental health interventions (DMHIs) in bridging the gap in adolescent mental health service delivery in Nigeria. DMHIs including mobile health applications, internet-based cognitive behavioural therapy, telepsychiatry, and short message services offer scalable, accessible, and cost-effective approaches to care. Evidence suggests that these interventions are effective in reducing symptoms of common mental disorders and improving treatment adherence, while also enhancing privacy and reducing stigma associated with help-seeking. The increasing penetration of mobile technology among Nigerian adolescents provides a unique opportunity to expand mental health access, particularly in underserved and rural communities. However, several barriers persist, including digital literacy gaps, infrastructural limitations, cultural beliefs, and concerns regarding data privacy and regulatory oversight. Findings indicate that while DMHIs hold significant promise, they are most effective when integrated with existing healthcare systems rather than used as standalone solutions. Addressing systemic challenges and strengthening policy frameworks will be essential for sustainable implementation.